Entangled photon virtual-state spectroscopy (2017)
In recent years, the process of absorbing two photons using a non-classical light sources has been studied thoroughly. In particular, it has been experimentally demonstrated that the absorption cross section of two entangled photons is much greater than the absorption cross section of two uncorrelated photons. In this dissertation a source of entangled photons produced through spontaneous parametric down conversion or SPDC was constructed and characterized. It was found that for a pump laser of 411.32 nm and a BBO crystal of 1 mm the produced photons followed the same optical path as the laser, it was also found that the joint spectrum is symmetric at the degenerate wavelength of 822 ± 0.5 nm. This work conclude by showing a first approximation to execute a measurement of the Hong-Ou-Mandel effect. The objective of the measurements of joint spectrum and the Hong-Ou-Mandel effect are to understand the correlation properties of the photon source, with this information a virtual state spectroscopy technique can be implemented on the experiment constructed